2020
DOI: 10.1097/mpg.0000000000002553
|View full text |Cite
|
Sign up to set email alerts
|

Adherence, Medical Outcomes, and Health Care Costs in Adolescents/Young Adults Following Pediatric Liver Transplantation

Abstract: Objective: Improved outcomes after pediatric liver transplantation (LT) have led to increasing numbers of adolescent and young adult recipients entering into adult health care systems. The aim of this study was to evaluate the impact of transition from pediatric to adult health care models on medical outcomes, measures of adherence, and health care utilization for pediatric LT recipients. Methods: We evaluated the course of patients who received an LT w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…6 Recent singlecenter studies of pediatric LT recipients also reported alarmingly high death rates after transition, 28% of 32 young adults in New York, and 28% of 64 in Atlanta. 7,8 In the latter group, 55% of deaths occurred within 5 years after transition of care. 8 Although our data confirm that young adulthood is a vulnerable time across transplant centers, the OPTN registry unfortunately does not include data on transition of care from the pediatric to an adult center, so we were not able to specifically evaluate the impact of this transition on lost to follow-up, graft dysfunction, or graft loss.…”
Section: Lack Of Specificity In Cause Of Death Reporting Hindered Inter-mentioning
confidence: 99%
“…6 Recent singlecenter studies of pediatric LT recipients also reported alarmingly high death rates after transition, 28% of 32 young adults in New York, and 28% of 64 in Atlanta. 7,8 In the latter group, 55% of deaths occurred within 5 years after transition of care. 8 Although our data confirm that young adulthood is a vulnerable time across transplant centers, the OPTN registry unfortunately does not include data on transition of care from the pediatric to an adult center, so we were not able to specifically evaluate the impact of this transition on lost to follow-up, graft dysfunction, or graft loss.…”
Section: Lack Of Specificity In Cause Of Death Reporting Hindered Inter-mentioning
confidence: 99%
“…Adherence to prescribed medications may represent one of the few modifiable risk factors to prevent graft loss in these patients. Autoimmune liver disorders have been reported among the highest causes of graft loss and mortality in young adults during the transition of care, ( 36 ) and most children with end‐stage liver disease from PSC are teenagers who transition care to adult programs soon after LT. Unfortunately, out of the scope of this retrospective study is the impact of patient nonadherence to immunosuppression on rPSC and graft dysfunction, but it is a formidable topic for future study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the success in PLT is also accompanied by additional challenges. For example, because of the long-term patient survival and the development of test methods, more long-term problems have been discovered, such as the increased prevalence of medication non-adherence ( 2 ) and hepatitis-related fibrosis ( 3 ). Due to its effectiveness in treating various liver diseases, more conditions are requiring PLT, such as α1-Antitrypsin deficiency ( 4 ) and non-alcoholic fatty liver disease ( 5 ).…”
Section: Introductionmentioning
confidence: 99%